2008
DOI: 10.1271/bbb.80067
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Characterization, and Differential Expression of a Farnesyl-Diphosphate Synthase Gene from the Basidiomycetous FungusGanoderma lucidum

Abstract: A farnesyl-diphosphate synthase gene, designated GlFPS, was isolated from a triterpene-producing basidiomycetous fungus, Ganoderma lucidum. The GlFPS cDNA was found to contain an open reading frame of 1,083 bp, encoding a protein of 360 amino acids with a calculated molecular mass of 41.27 kDa. The deduced amino acid sequence of the GlFPS cDNA exhibited a high homology with other fungal FPS genes, and contained four conserved domains. Phylogenetic analysis showed that GlFPS belonged to the basidiomycete FPS gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…In 2014, the triterpenoid biosynthesis pathway in A. cinnamomea was validated through genomic and transcriptome analyses; this pathway is similar to the MVA pathway in Ganoderma lucidum [13]. Several enzymes, such as squalene synthase (SQS) [14], HMG-CoA reductase (HMGR) [15], mevalonate pyrophosphate decarboxylase (MVD) [16], and farnesyldiphosphate synthase (FPS) [17], are implicated in the MVA pathway. A previous study showed that the synthesis of triterpenoids in A. cinnamomea is complex.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, the triterpenoid biosynthesis pathway in A. cinnamomea was validated through genomic and transcriptome analyses; this pathway is similar to the MVA pathway in Ganoderma lucidum [13]. Several enzymes, such as squalene synthase (SQS) [14], HMG-CoA reductase (HMGR) [15], mevalonate pyrophosphate decarboxylase (MVD) [16], and farnesyldiphosphate synthase (FPS) [17], are implicated in the MVA pathway. A previous study showed that the synthesis of triterpenoids in A. cinnamomea is complex.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that G. lucidum has many biological and pharmacological activities that can be attributed to its complex chemical composition (Wang and Ng 2006;Mizushina et al 1998;Eo et al 1999). In addition to the studies on the pharmacological activities of G. lucidum, molecular genetics studies have also been conducted, resulting in the cloning and characterization of several of its genes (Ding et al 2008;Xu et al 2006;Shang et al 2008Shang et al , 2010Zhao et al 2007). Establishment of an efficient and convenient transformation method forms the basis for further functional studies of these genes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also proved that GAs yield was greatly influenced by a number of environmental factors including the elicitor, parameters of fermentation process and culture medium21464748.…”
Section: Discussionmentioning
confidence: 93%